The implementation and effectiveness of Indonesian Supreme Court Rule No. 3 of 2017 on women victims of the sexual violence in Yogyakarta - Anggraeny, Kurnia Dewi; Kamaludin, Aang; Khakim, Mufti; Sugiharto, Gatot (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2023)
PERMA (Supreme Court Rule) No. 3 of 2017 issued by the Supreme Court regulates the attitude guidelines for judges in adjudicating women's cases in conflict with the law, both criminal and civil cases involving women as victims, witnesses, or parties. These regulations can be used as a legal basis by judges in adjudicating cases of women in conflict with the law due to criminal acts of sexual violence. This research aims to determine the effectiveness of implementing PERMA No. 3 of 2017 concerning guidelines for adjudicating cases of women in conflict with the law as a result of victims of sexual violence at the Yogyakarta District Court. The method used in this research is empirical normative, which focuses on collecting information obtained from judges at the Yogyakarta District Court regarding the effectiveness of PERMA No. 3 of 2017 against women as a result of victims of sexual violence. The approach methods that the author uses in this research include the conceptual approach, the statutory approach, and the case approach. The data collection method is through interviews and documentation of judges, and the data analysis used is descriptive-qualitative. This research concludes that PERMA No. 3 of 2017 has been quite effective in accordance with the theory of legal effectiveness, which uses several a quo decisions as samples to determine whether PERMA No. 3 of 2017 has been applied and implemented in the Yogyakarta District Court for women victims of sexual violence.